POLITIK TUAN GURU VERSUS POLITIK MEDIA “PILPRES 2019 DI LOMBOK “ANTARA DAKWAH DAN POLITIK - AHSANUL RIJAL (Universitas Islam Negeri (UIN) Mataram, 2019)
The focus of this research is focused on two comparative variables between master teacher political communication and media politics in portraying the influence of religious authorities in media and media construction. The analysis is carried out by interpreting data in the form of videos, photos and interaction between netizens (interction of society) in understanding ideology and social identity. Media messages are adapted to the context of social reality when the message is made. Since all messages are the social and cultural production of the community, this is what is called qualitative content analysis. The results of this study, Tuan guru as a local level political communicator element will be considered comparative with the media political communication style, because the different functions of master teachers in practical politics cannot provide a change in the political ijtihad of Lombok society by persuasively. In fact, master and politics in the view of the dichotomous sasak-Lombok society, because the community of internet users has been constructed with digital distortion, so that a broad window to believe in their choices ideologically without intervention. The function of social media in political communication provides a new discourse in communication studies, so that religious authority that has been built massively, systematically and structurally is displaced by the authoritative function of the media in its construction.